Rational design of drug delivery systems for potential programmable drug release and improved therapeutic effect. (7th May 2019) - Ding, Yuxun; Liu, Jinjian; Li, Xue; Xu, Linlin; Li, Chang; Ma, Lin; Liu, Jianfeng; Ma, Rujiang; An, Yingli; Huang, Fan; Liu, Yang; Shi, Linqi
Abstract : pH-Reduction dual responsive nanocarriers (DRNs) achieve programmable release of CA4 and CDDP in cancer therapy. Abstract : Nanoparticle-based combination therapy has been reported as one important treatment strategy to improve the therapeutic efficacy in cancer therapy. However, the traditional co-delivery method often suffers from serious coordination issues that fail to account for the differences in the action sites of each of the drugs, greatly counteracting the synergistic effects of combination agents. Herein, we report a pH-reduction dual responsive drug delivery system for the programmable release of combretastatin A-4 (CA4) and cis -platinum (CDDP). According to their spatial and temporal needs, such nanocarriers could firstly release CA4 in the perivascular sites by responding to the acidic microenvironment of the tumor, then further diffuse throughout the tumor and release CDDP upon redox when being taken-up by the cancer cells. With the help of such spatiotemporal release properties, CA4 and CDDP can target the endothelial cells of tumor vessels and the cancer cells in succession, giving rise to temporal and spatial synergisms. On one hand, the first released CA4 provided a complementary effect for improving tumor accumulation of nanocarriers and the delivery effect of CDDP. On the other hand, CA4 and CDDP respectively targeted their action sites, overall maximizing the therapeutic effect. More importantly, such spatiotemporal drug delivery ability is accomplished by the pH-reduction dual responsive design of the nanocarriers, and thus could also serve as a universal approach for programmable release of other combination agents to improve their synergistic effect in cancer therapy.